2019
DOI: 10.1038/s41598-019-55531-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the enzymatic activity of the serine protease domain of Factor VII activating protease (FSAP)

Abstract: Factor VII (FVII) activating protease (FSAP) is a circulating serine protease. Human genetic studies, based on the Marburg I (MI) (Gly221Glu, chymotrypsin numbering system) polymorphism, implicate FSAP in the pathogenesis of many diseases. Here, we describe the molecular and functional changes caused by the Gly221Glu substitution in the 220 loop using recombinant proteins expressed in E. coli. The serine protease domain (SPD) of wild type (WT) FSAP displayed auto-catalytic activation whereas the MI isoform dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This indirectly implicates FSAP in the outcome of stroke in mouse models. We have recently expressed the recombinant serine protease domain (SPD) of human FSAP and confirmed that it recapitulates all, the tested, activities of the endogenous full-length protein 25 . Here, we report on the efficacy of FSAP-SPD treatment in mouse models of ischemic stroke.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This indirectly implicates FSAP in the outcome of stroke in mouse models. We have recently expressed the recombinant serine protease domain (SPD) of human FSAP and confirmed that it recapitulates all, the tested, activities of the endogenous full-length protein 25 . Here, we report on the efficacy of FSAP-SPD treatment in mouse models of ischemic stroke.…”
Section: Introductionmentioning
confidence: 74%
“…WT-SPD provoked a hemostasis response, most probably, due to the inactivation of tissue factor pathway inhibitor 12,25 . The seemingly incongruent effects; the ability to promote coagulation and, at the same time, improve stroke outcome can be reconciled with the hypothesis that in the stroke model the pro-fibrinolytic effect of FSAP predominates over the pro-coagulant effect leading to an overall positive outcome.…”
Section: Resultsmentioning
confidence: 99%
“…14,60 In contrast, the large hydrophobic side chain of Met156 in factor VII and factor VII activating protease (an enzyme with some homology to FXII and pro-HGFA) would not be expected to stabilize an open active site conformation in the zymogen. 60,71 Indeed, Met156 may contribute to the zymogen-like behavior of the activated form of FVII (FVIIa) when it is not bound to its cofactor tissue factor. Petrovan and Ruf replaced Met156 in factor VIIa with glutamine and noted increased protease activity in the absence of tissue factor.…”
Section: Con Clus I On S and Future Cons Ider Ationsmentioning
confidence: 99%
“…Modeling of the FXII and PK protease domains based on the tPA structure suggests that Gln156 can coordinate with the Asp194 carboxylate to weakly stabilize an open active site conformation through hydrogen bonding 14,60 . In contrast, the large hydrophobic side chain of Met156 in factor VII and factor VII activating protease (an enzyme with some homology to FXII and pro‐HGFA) would not be expected to stabilize an open active site conformation in the zymogen 60,71 . Indeed, Met156 may contribute to the zymogen‐like behavior of the activated form of FVII (FVIIa) when it is not bound to its cofactor tissue factor.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 99%
“…The Marburg I (MI) single nucleotide polymorphism in the FSAPencoding gene leads to an amino acid exchange in the serine protease domain of FSAP and inactivation of the enzyme [12]. This may be due to a defect in the conversion from the zymogen to the active enzyme [13,14]. This polymorphism is a risk factor for carotid stenosis [15], stroke [16] as well as liver fibrosis [17].…”
Section: Introductionmentioning
confidence: 99%